Prácticas éticas y su importancia en el ejercicio profesional de las secretarias ejecutivas en el Gobierno Autónomo Descentralizado Municipal del Cantón San Francisco de Puebloviejo - Villalta Marmolejo, Jennifer Magdalena (2020)
The present case study was conducted with the theme: Ethical practices and their importance in the professional practice of the Executive Secretaries in the Autonomous Decentralized Municipal Government of the Canton San Francisco the Puebloviejo, which is an organization of governmental organization for the development of this analysis was carried out the deductive method because it is knowledgeable to obtain general knowledge, based on a particular fact that was obtained through a survey that helps to gather relevant and necessary information, whose objective is to establish how ethical practices impact and their importance in the exercise Executive secretaries professional results recorded as a result that ethical practices is one of the problems that is affecting the development of the activities carried out by the secretaries and administrators of the department of human talent, since a newspaper coexists with activities and interper relationships Therefore, it can be concluded that professional performance is one of the most important factors that every employee or administrative secretary must develop with efficiency efficiency and effectiveness within their work space, since it is of utmost importance to maintain proper organization and allow staff to establish a dialogue with emotional clients so that they have a good working environment so that the level of effective professionalism can be achieved.